ONE STOP CENTRES FOR SURVIVORS OF SEXUAL VIOLENCE IN INDIA: IT’S TIME FOR SWOT ANALYSIS TO OVERCOME THE BARRIERS (Journal of Forensic Medicine & Toxicology, 2024)
The Government of India (GoI) launched the “One Stop Centre” (OSC) in 2015 to offer support and help to women afflicted by violence (Gender Based Violence, Domestic Violence, and Sexual Violence). It is present throughout the country at the district level and provides a range of services, including emergency medical care, police support, assistance with legal matters, counselling, short-term accommodation, and help with survivors’ rehabilitation for women who have been abused. According to the Press Information Bureau and Mission Sakthi Scheme,out of the 733 approved OSC for 730 districts (encompassing 35 States and Union Territories), 704 centres were operational, and 6,99,405 women received assistance till March 31, 2023. 1,2
Keywords: launched; police support; Violence